Bank Bonuses and Bail-out Guarantees - Hendrik Hakenes; Isabel Schnabel (Verein für Socialpolitik, 2010)
This paper analyzes how a bank shareholder optimally designs the compensation scheme of a bank manager if there are agency problems between the shareholder and the manager, and how this design changes in reaction to anticipated bail-outs. If there is a problem of excessive risk-taking, bail-out guarantees lead to steeper compensation schemes and even more risk-taking. If there is an effort problem, the compensation scheme becomes flatter and effort decreases. If both types of agency problems are present, a sufficiently large increase in bail-out perceptions will make it optimal for a welfare-maximizing regulator to impose ceilings on bank bonuses.
Keywords: G21; G28; M52; 330; Bonus payments; bail-out guarantees; bank manager compensation